2015
DOI: 10.3389/fmars.2015.00106
|View full text |Cite
|
Sign up to set email alerts
|

Microbially-Mediated Fluorescent Organic Matter Transformations in the Deep Ocean. Do the Chemical Precursors Matter?

Abstract: The refractory nature of marine dissolved organic matter (DOM) increases while it travels from surface waters to the deep ocean. This resistant fraction is in part composed of fluorescent humic-like material, which is relatively difficult to metabolize by deep water prokaryotes, and it can also be generated by microbial activity. It has been recently argued that microbial production of new fluorescent DOM (FDOM) requires the presence of humic precursors in the surrounding environment. In order to experimentall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 85 publications
0
11
0
Order By: Relevance
“…The production rates of microbial humic-like fluorophore differ among substrates used in the incubation of marine bacterial communities (Jørgensen et al, 2014; Aparicio et al, 2015). For example, Aparicio et al (2015) found that the production rates of marine humic-like fluorophore during the incubation of marine bacterial communities with Suwannee River humic acids were higher than those with glucose and acetate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The production rates of microbial humic-like fluorophore differ among substrates used in the incubation of marine bacterial communities (Jørgensen et al, 2014; Aparicio et al, 2015). For example, Aparicio et al (2015) found that the production rates of marine humic-like fluorophore during the incubation of marine bacterial communities with Suwannee River humic acids were higher than those with glucose and acetate.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Aparicio et al (2015) found that the production rates of marine humic-like fluorophore during the incubation of marine bacterial communities with Suwannee River humic acids were higher than those with glucose and acetate. Using different substrates for microbial community incubation reportedly cause changes in microbial community structure and/or bacterial physiology (Gómez-Consarnau et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Peaks A, M and C correspond to humic-like substances, and peak T corresponds to protein-like substances. FDOM was measured as detailed in (Aparicio et al, 2015). Table S1.…”
Section: Supporting Informationmentioning
confidence: 99%